Expediente e apresentação da edição - Afonso, Mariângela da Rosa; Ilha, Franciele Roos da Silva; Ribeiro, José Antonio Bicca; Siebiger, Ralf Hermes (Eventos Pedagógicos, 2025)
Expediente e apresentação da edição - v. 16, n. 2, ago./out. 2025.